NATIONAL TRADITIONS OF INGUSH GIRLS UPBRINGING: IN THE PAST AND PRESENT - Getagazova, Asa Magomedovna (History, Archeology and Ethnography of the Caucasus, 2023)
The upbringing of Ingush girls is a poorly studied topic in the field of science. Researchers have addressed it in the context of family and traditions, but there have been no gender-specific studies to date. In this article, the author focuses on the changes that have taken place in the traditions of raising Ingush girls, using the method of comparing their archaic and modern forms. The author demonstrates how the traditions of raising girls were transformed under the influence of socialist perestroika, urbanization, the growth of the socio-economic well-being of the Ingush region, as well as the re-Islamization of the nation that occurred in recent decades. For an objective and complete consideration of the topic, the author used both works of historians, as well as her own field data collected during interviews with residents of the villages Dzheirakh, Srednie Achaluki, Plievo, Altievo and towns Karabulak and Sunzha of the Republic of Ingushetia in 2020-2023. Applying comparative and descriptive methods, the author introduces the educational traditions for girls that have disappeared from the practices of the Ingush, identifies the changes that have occurred in some of them, and also notes the emergence of new ones. The relevance of this study is due to the lack of the necessary evidence-based information regarding the national traditions of raising Ingush girls at various stages of their life cycle. Moreover, given the tendency to destroy the institution of the family and the gender-role self-awareness of the younger generations, which is emerging today against the backdrop of modern globalization processes, the study and promotion of national methods of education acquires great scientific and practical significance.
Keywords: Ingush girl; mother; family; childhood; upbringing; tradition; urbanization; re-Islamization